Small loans make a big difference - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Access to microcredit can help farmers weather leaner times and enable rural entrepreneurs to seize economic opportunities. Many financial institutions are realising that small-scale customers are not only a large market, but a profitable one too.